2024
DOI: 10.3390/diagnostics14030242
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Analysis in Rheumatological Diseases with Neuropsychiatric Complications and Manifestations: A Narrative Review

Massimiliano Castellazzi,
Raffaella Candeloro,
Maura Pugliatti
et al.

Abstract: The analysis of cerebrospinal fluid (CSF) remains a valuable diagnostic tool in the evaluation of inflammatory and infectious conditions involving the brain, spinal cord, and meninges. Since many rheumatic inflammatory diseases can involve the central and peripheral nervous system, the aims of this narrative review were to summarize the latest evidence on the use of CSF analysis in the field of neuropsychiatric manifestations of rheumatic diseases. Routine CSF parameters were taken into consideration for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
(145 reference statements)
0
0
0
Order By: Relevance
“…The hypothesis that sex differences in body height, resulting in a greater spine length and consequently an increased distance for cerebrospinal fluid (CSF) flow in males compared to females, has been posited as a potential explanation for the observed disparity in QAlb values between the sexes [ 34 ]. However, our recent study revealed that even after controlling for patients’ height, the independent association of QAlb and CSF TP values with sex remains statistically significant [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that sex differences in body height, resulting in a greater spine length and consequently an increased distance for cerebrospinal fluid (CSF) flow in males compared to females, has been posited as a potential explanation for the observed disparity in QAlb values between the sexes [ 34 ]. However, our recent study revealed that even after controlling for patients’ height, the independent association of QAlb and CSF TP values with sex remains statistically significant [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absence of associations between QAlb and CSF protein concentrations with BMI was further confirmed in a multi-comparison analysis in males and females grouped by BMI weight status. No differences emerged when comparing underweight, normal weight, overweight and obese subjects in the two sexes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%